Madeiras do estado de Mato Grosso : identificação, comercialização e utilização - Zaque, Leonardo Antônio Moraes (2018)
The state of Mato Grosso is one of the main producers of tropical sawn timber in Brazil. Thus, this study aimed to evaluate the characterization of the timber trade in the State of Mato Grosso and describe macroscopic characteristics of the species traded subsidizing identification processes. In the first chapter evaluated the commercialization of the main timber species in the region between 2007 and 2014, besides the main products generated by these species and their uses. For this, the reports of beneficiation and trade in wood products of the State Secretariat of Environment of Mato Grosso (SEMA-MT) were used. The most traded species during the period in terms of volume were Erisma uncinatum (11.47%), Qualea sp. (10.16%) and Goupia glabra (7.32%). In the second and third chapters the macroscopic characteristics and colorimetric characterization were evaluated, respectively, of the 30 most commercialized timber species in the state of Mato Grosso. The macroscopic description was made for the three axes of the wood (transverse, radial and tangential). From the dichotomous key one can observe the main anatomical elements to distinguish the species. The main parameters responsible for species differentiation were the parenchyma types and the pores (arrangement, size and obstruction). The most frequent parenchyma were aliform, confluent aliform and vasicentric. The colorimetric characterization was performed by means of a spectrophotometer, which was used to directly read the color of the samples in the tangential and transverse planes. From these readings were obtained colorimetric parameters (brightness, hue and saturation) of the timber. The specific mass was also determined to perform clustering together with the colorimetric parameters. The woods had a tendency to be more yellow than red and the cross section obtained darker coloring than the tangential section. The lighter woods presented smaller specific masses, and the darker ones obtained larger specific masses.